Platelet-Rich Plasma Augmentation for Hip Arthroscopy - Mannava, Sandeep (Arthrosc Tech, 2017)
Biological augmentation and therapeutics are being increasingly used in musculoskeletal and orthopaedic care. Platelet-rich plasma (PRP) is produced from centrifugation of peripheral blood, a process that concentrates platelets within autologous plasma. The process of PRP preparation is fundamental in controlling the contents, and it influences its therapeutic potential. Platelets contain alpha granules that store and release a variety of growth factors and other proteins that may augment the healing environment; PRP also has the added benefit of promoting postsurgical hemostasis. The purpose of this report was to detail our institutional preparation protocol and method of administration of PRP during hip arthroscopy.